Caveolin-1 in Kidney Chronic Antibody-Mediated Rejection: An Integrated Immunohistochemical and Transcriptomic Analysis Based on the Banff Human Organ Transplant (B-HOT) Gene Panel - Alessandro Gambella; Antonella Barreca; Simona Osella-Abate; Emanuel Bottasso; Manuela Maria Giarin; Mauro Papotti; Luigi Biancone; Jasna Metovic; Giammarco Collemi; Paola Cassoni; Luca Bertero (Biomedicines, 2021)
Caveolin-1 overexpression has previously been reported as a marker of endothelial injury in kidney chronic antibody-mediated rejection (c-ABMR), but conclusive evidence supporting its use for daily diagnostic practice is missing. This study aims to evaluate if Caveolin-1 can be considered an immunohistochemical surrogate marker of c-ABMR. Caveolin-1 expression was analyzed in a selected series of 22 c-ABMR samples and 11 controls. Caveolin-1 immunohistochemistry proved positive in peritubular and glomerular capillaries of c-ABMR specimens, irrespective of C4d status whereas all controls were negative. Multiplex gene expression profiling in c-ABMR cases confirmed Caveolin-1 overexpression and identified additional genes (n = 220) and pathways, including MHC Class II antigen presentation and Type II interferon signaling. No differences in terms of gene expression (including Caveolin-1 gene) were observed according to C4d status. Conversely, immune cell signatures showed a NK-cell prevalence in C4d-negative samples compared with a B-cell predominance in C4d-positive cases, a finding confirmed by immunohistochemical assessment. Finally, differentially expressed genes were observed between c-ABMR and controls in pathways associated with Caveolin-1 functions (angiogenesis, cell metabolism and cell–ECM interaction). Based on our findings, Caveolin-1 resulted as a key player in c-ABMR, supporting its role as a marker of this condition irrespective of C4d status.